Dickson's Method for Generating Pythagorean Triples Revisited (European Journal of Pure and Applied Mathematics, 2017)
The Dickson's method for generating Pythagorean triples states that the integers $a=r+s$, $b=r+t$,Â  $c=r+s+t$ form a Pythagorean triple $(a,b,c)$ on condition that $r^2=2st$, where $r,s,t$ are positive integers, \cite{DICKSON}. This paper presents a new simple proof of this method.